Gambaran Pola Perilaku Pencarian Pengobatan Penyakit ISPA pada Balita di Desa Nuaja Puskesmas Riaraja Ende - Antonia Hari; Deviarbi S. Tira; Sarci M. Toy (Universitas Nusa Cendana, 2019)
Acute respiratory infections (ARI) is an acute respiratory tract infection that attacks the throat, nose and lungs that lasts approximately 14 days and about the structure of the duct above the larynx. There are various behavioral treatments for diseases in Indonesia, such as using medicines purchased at market without a doctor's prescription (swamedication), using traditional materials in the surrounding environment or asking shamans for help, if they have not succeeded then the community will go to a medical health service. This is because Indonesia has a source of treatment covering three interrelated sectors namely self-medication, self-medication, medical treatment and traditional medicine. This study is aiimed at determinining the pattern of behavior seeking treatment of ARI for toddlers at Nuaja Village, the Working Area of Riaraja Ende Health Center in 2019. This research is a qualitative research with a phenomenological approach. The core informant in this study is mothers who have toddlers aged 2-5 years and the supporting informants are the traditional healerd community, and health workers. The results show that public knowledge about the seeking behavior for the treatment of ARI is good. The priorit community end to seek traditional treatment. If the community does not recover after traditional treatment, the community will seek treatment from medical staff. Suggestions from the study are expected by health workers to carry out health promotion regarding self-medication and combination treatment with material that is appropriate to the behavior of local mothers of toddlers.